Pengaruh inovasi Produk, Keunggulan Bersaing, dan Strategi Pemasaran Terhadap Kinerja Pemasaran - Shintia Ningrum; Valen Desliena Fitra; Vicky F Sanjaya (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Product innovation, competitive advantage and marketing strategy are indicators to measure the success and success of managing a business. Because product innovation and product excellence are variables that are believed to be able to improve marketing performance, especially for micro, small and medium enterprises (UMKM). The purpose of this study was to directly test the variables of product innovation, competitive advantage and marketing strategy on marketing performance. To consumers. The number of samples included in this study was 82 and PLS3 was used as an analysis tool. The results showed that the effect of product innovation, competitive advantage, and marketing strategy had a positive effect on marketing performance.